2007
DOI: 10.1177/0269216307083386
|View full text |Cite
|
Sign up to set email alerts
|

Assessing physical functioning: a systematic review of quality of life measures developed for use in palliative care

Abstract: Despite its importance, PF assessment seems to be a minor part of palliative care QoL instruments. Clear definitions and conceptualization of PF are needed, as well as a consensus on relevant aspects to include in improved instruments. Performance scales already developed should be further explored with regard to content, validity and psychometric properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 54 publications
0
48
0
2
Order By: Relevance
“…The functionality loss and the fear of turning into a burden for the caregiver and the family are frequent concerns that are continuously mentioned among the reasons to desire the end of life. 31 The objective of rehabilitation in PC is to improve the patients' quality of life, helping them to achieve their full physical, psychological, social, vocational and cognitive potential with as little dependence as possible, independently of the life expectancy. To achieve this objective, many elements are highlighted in the studies, such as: setting realistic goals, multidisciplinary teamwork, ability to react rapidly to emerging needs, among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functionality loss and the fear of turning into a burden for the caregiver and the family are frequent concerns that are continuously mentioned among the reasons to desire the end of life. 31 The objective of rehabilitation in PC is to improve the patients' quality of life, helping them to achieve their full physical, psychological, social, vocational and cognitive potential with as little dependence as possible, independently of the life expectancy. To achieve this objective, many elements are highlighted in the studies, such as: setting realistic goals, multidisciplinary teamwork, ability to react rapidly to emerging needs, among others.…”
Section: Discussionmentioning
confidence: 99%
“…33 Nevertheless, an increasing number of studies guarantees that rehabilitation works towards many unsatisfied needs of the PC patients and, although it does not eliminate the damage the diseases cause, it can certainly mitigate them. 22,[31][32][33][34] In addition, it seems to unite patients and their families through a common objective, that is, to act against the functional decline so that it is not experienced in a solitary manner, isolated from the family and the health team.…”
Section: Discussionmentioning
confidence: 99%
“…An indication of this is that the number of health-related quality-of-life questionnaires available for French palliative practice is small [32]. For this reason, it is important to develop adapted tools.…”
Section: Discussionmentioning
confidence: 99%
“…In English language there are a lot of interesting questionnaires specifically adapted to our population [20][21][22]. After a literature review, we identified two questionnaires that take into account the specific QoL concerns of the end of life: the Missoulas-Vitas Quality Of Life Index (MVQOLI) and the QUAL-E (Quality of Life at the End of Life Measure).…”
Section: Introductionmentioning
confidence: 99%
“…Disease modifying and symptom relieving treatments often leads to sedations, fatigue, physical inactivity, loss of mobility, increased dependency in daily activities and hospitalizations, eventually reducing patient autonomy and QoL. Hence, a multi modal approach comprising enhanced physical intervention is needed to decelerate reduction in physical performance and alleviate other problems [42,43].…”
Section: Physical Therapy Interventions and Cancer Painapplications mentioning
confidence: 99%